Histoplasmosis in the Republic of Congo dominated by African histoplasmosis, Histoplasma capsulatum var. duboisii. - Fructueux Modeste Amona; David W Denning; Donatien Moukassa; Michel Develoux; Christophe Hennequin (PLoS Neglected Tropical Diseases)
The Republic of Congo (RoC) is one of the African countries with the most histoplasmosis cases reported. This review summarizes the current status regarding epidemiology, diagnostic tools, and treatment of histoplasmosis in the RoC. A computerized search was performed from online databases Medline, PubMed, HINARI, and Google Scholar to collect literature on histoplasmosis in the RoC. We found 57 cases of histoplasmosis diagnosed between 1954 and 2019, corresponding to an incidence rate of 1-3 cases each year without significant impact of the AIDS epidemic in the country. Of the 57 cases, 54 (94.7%) were cases of Histoplasma capsulatum var. duboisii (Hcd) infection, African histoplasmosis. Three cases (5.3%) of Histoplasma capsulatum var. capsulatum infection were recorded, but all were acquired outside in the RoC. The patients' ages ranged between 13 months to 60 years. An equal number of cases were observed in adults in the third or fourth decades (n = 14; 24.6%) and in children aged ≤15 years. Skin lesions (46.3%), lymph nodes (37%), and bone lesions (26%) were the most frequent clinical presentations. Most diagnoses were based on histopathology and distinctive large yeast forms seen in tissue. Amphotericin B (AmB) was first line therapy in 65% of the cases and itraconazole (25%) for maintenance therapy. The occurrence of African histoplasmosis in apparently normal children raises the possibility that African histoplasmosis is linked to environmental fungal exposure.